An unusual case of yawning during sleep associated with sleep bruxism and obstructive sleep apnea–a case report - Michałek, Monika; Marschollek, Karol; Kuliczkowski, Wiktor; Waliszewska-Prosół, Marta; Wojakowska, Anna; Madziarska, Katarzyna; Martynowicz, Helena (Frontiers in Medicine, 2025)
The current case report presents an unusual coincidence of yawning and sleep bruxism during sleep in a patient with obstructive sleep apnea (OSA). Both conditions were previously defined in the literature as challenging, multidisciplinary problems with complex and little-known pathogenesis. A 71-year-old man with a history of coronary artery disease underwent video-polysomnography (vPSG) due to the suspicion of OSA. vPSG results confirmed severe obstructive sleep apnea, sleep bruxism, and frequent episodes of yawning during sleep. Therapeutic intervention included positive airway pressure therapy and resulted in the resolution of apneic events. Interestingly, PAP titration also reduced the frequency of episodes of sleep bruxism and yawning. Results of the current case report suggest a temporal relationship between desaturation and yawning episodes, thus indicating the hypoxic basis for this behavior. Resolution of yawning after PAP therapy appears consistent with this theory. An instrumental approach to OSA diagnosis supplemented by video-recording allowed the diagnosis of the unusual presence of yawning during sleep.